2019
DOI: 10.1016/j.whi.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation among Female and Male Veterans before and after a Randomized Trial of Proactive Outreach

Abstract: Introduction: Female veterans smoke cigarettes at high rates compared with both male veterans and nonveteran women. Proactive outreach to smokers may reduce gender disparities in cessation care. The objectives of this study were to compare baseline experiences with VA smoking cessation care for men and women and to assess for gender differences in response to a proactive outreach intervention. Methods: We conducted a post hoc subgroup analysis of a pragmatic, multisite randomized, controlled trial comparing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To better serve women Veterans, the VA has developed women's health clinics with designated women's health providers, mental health clinics with dedicated women's health providers, and genderspecific education materials on tobacco cessation for healthcare providers and patients [15,16]. Despite these advances, studies have shown that women Veterans are less likely to be satisfied with cessation care received at the VA compared to male Veterans [17] and the organizational measures implemented by the VA were not associated with improved treatment rates or reduced gender differences in smoking [13]. A recent chart review showed that only half of women Veterans who were referred to the William S. Middleton Memorial VA's Tobacco Cessation Clinic ever followed through with enrollment, but did not examine why [18].…”
Section: Introductionmentioning
confidence: 99%
“…To better serve women Veterans, the VA has developed women's health clinics with designated women's health providers, mental health clinics with dedicated women's health providers, and genderspecific education materials on tobacco cessation for healthcare providers and patients [15,16]. Despite these advances, studies have shown that women Veterans are less likely to be satisfied with cessation care received at the VA compared to male Veterans [17] and the organizational measures implemented by the VA were not associated with improved treatment rates or reduced gender differences in smoking [13]. A recent chart review showed that only half of women Veterans who were referred to the William S. Middleton Memorial VA's Tobacco Cessation Clinic ever followed through with enrollment, but did not examine why [18].…”
Section: Introductionmentioning
confidence: 99%
“…The included works stem from not only trials (Danan, Sherman, et al, 2019a) and cohort studies (Dursa et al, 2019;Harrington et al, 2019;Naylor et al, 2019;Brown et al, 2019), but also clinical program evaluations (Kumpula et al, 2019), VA patient experience surveys (Breland et al, 2019), and research process metrics (Goldstein et al, 2019). Multiple VA research entities are represented in this collection, including the Cooperative Studies Program (e.g., Harrington et al, 2019;Brown et al, 2019), the VA Evidence Synthesis Program (Danan, Ullman, et al, 2019b), Health Services Research & Development (Combellick et al, 2019;Danan, Sherman, et al, 2019a;Goldstein et al, 2019), and Mental Illness Research Education Clinical Centers of Excellence (Naylor et al, 2019). Bovin et al exemplify the usefulness of combining the VA's array of data sources, including electronic medical record and research survey data, to produce clinically important findings related to MST screening.…”
Section: Discussionmentioning
confidence: 99%
“…Three articles dive deeper into specific areas of health and health behaviors with potential gender differences. First, Danan, Sherman, et al (2019a) examined gender differences in smoking cessation when exposed to a proactive treatment regimen versus usual care. They found that, compared with men, women were less satisfied with the process for obtaining smoking cessation medications.…”
Section: Health Conditions and Health Behaviorsmentioning
confidence: 99%
“…32 This exploratory study examined differences in smoking motives and SOC among Veterans with past-year smoking, which to our knowledge has not been previously studied. Based on prior research among Veterans indicating gender differences between men and women on smoking status outcomes, 27,33 we also conducted stratified analyses by gender and then compared LGB Veterans to heterosexual Veterans.…”
Section: Stages Of Change (Soc) In Smoking Cessationmentioning
confidence: 99%